EFFECT OF SEDIMENT PARTICLE SIZES ON THE DENSITY AND MORPHOMETRIC SEAGRASS LEAF (Enhalus acoroides) IN JAGO-JAGO SEA WATERS OFTAPANULI TENGAH NORTH SUMATERA - Sibarani, Rosari; Zulkifli, Zulkifli; Tanjung, Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT ThisresearchhasbeenheldonMarch-April2019inJago-Jago sea waters of Tapanuli Tengah, North Sumatera. Thepurposeofthisstudy wastodeterminethedensity ofspecies, morphometricsofEnhalus acoroidesleaves. Thestudy wasalsoaimedto analyzetheeffect of sediment particle sizesondensity andmorphometricsofseagrass leaves. Thestationsweredetermined by purposivesamplingandusetransectline methodfortaken sample. The results of this study showed that the highest density was found in Station II which had very coarse sand sediment particles, coarse sand, medium sand and fine sand with a value of 33,99 stands / m2and the lowest density is found in Station III which has very coarse sand sediment particles and coarse sand with a value of 31,88 stands / m2. Morphometric average length of seagrass leaves the longest at Station II with a value of 36,90 cm and the shortest at Station I with a value of 32,29 cm. Morphometric average width of seagrass leaves at Station II with a value of 1,60 cm and the shortest at Station I and III with a value of 1,50 cm. The result ofsimple linear regression test results of the effect of sediment particle size on the density and morphometrics of seagrass leaves with R2(coefficient of determination) = 0,44; 0,22; 0,35 indicate the effect of sediment particle size on the density and morphometrics of seagrass leaves Enhalus acoroides.    Keyword: Sediment Particle Sizes, Seagrass, Density, Morphometrics